STUDY THE OPTICAL PROPERTIES OF POLYVINYLPYRROLIDONE (PVP) DOPED WITH KBr - Hussein Hakim; Ahmed Hashim; Ghaidaa Abdul-Hafidh; .H.A Alyaa; Saif Mohammed (European Scientific Journal, ESJ, 2014)
The pure polyvinylpyrrolidone (PVP) and (PVP-KBr) composite with different weight percentage of KBr were prepared using solution casting technique. The optical properties of randomly mixed system consisting of PVP and KBr powders were studied. The effect of KBr concentration on the optical properties of (PVP-KBr) composites have been investigated. The experimental results show that the optical constants (Refractive index, Extinction coefficient, Real and Imaginary parts of the dielectric constant) showed clear changes with increasing the doping concentrations.